Using palynomorphological characteristics for the identification of species of Alsinoideae (Caryophyllaceae): a systematic approach. Issue 3 (4th May 2019) - Ullah, Fazal; Nasar Shah, Syed; Zaman, Wajid; Zafar, Muhammad; Ahmad, Mushtaq; Ayaz, Asma; Sohail, Aamir; Saqib, Saddam
Abstract: Palynological characters of 18 species belonging to seven genera of the traditional subfamily Alsinoideae including Arenaria, Cerastium, Eremogone, Lepyrodiclis, Minuartia, Sabulina and Stellaria were studied in detail using light and scanning electron microscopy. Pollen grains of subfamily Alsinoideae are subspheroidal or prolate, pantoporate and 20.04 to 51.4 µm in size, prominent and sunken apertures uniformly distributed on the pollen surface. Two types of pollen grain ornamentation were observed, i.e. microechinate-punctate or microechinate-perforate. Echini are present on the surface of the pollen of all investigated species with medium, dense, or sparse echinodensity. These species exhibit variation in polar view, equatorial diameter, number of apertures, exine thickness, diameter of pore, appendages per pore, pore ornamentation, echini arrangement, echinidensity and shape of pollen. Based on qualitative characters, a dichotomous key has been developed for quick and easy identification. The present investigation contributes to the systematic approach using palynological characteristics and correct identification of species for members of subfamily Alsinoideae (Caryophyllaceae).